Effect of Rushton impeller speed on biogas production in anaerobic digestion of continuous stirred bioreactor - Sinaga, Nazaruddin; Hatta, Kurnia; Ahmad, Nurjehan Ezzatul; Mel, Maizirwan (Penerbit Akademia Baru, 2018)
The formation of biogas in an anaerobic digester is a complex fermentation process of organic compounds involving microorganisms. The biogas production can be enhanced by using a mixer, which depends on its rotational speed. This study investigated the effect of mixer rotational speed on biogas production in an anaerobic continuous stirred bioreactor with a computational approach. The purpose of this study is to find the optimum speed of the mixer that produces the highest biogas production. The finite volume method is used to simulate the synthropic digestion process experienced by volatile fatty acids in a three-phase form. The mixer used is from the Rushton impeller type, which rotates with speed variations of 50, 70, 100, 150, 200, and 300 rpm. The process takes place at temperature of 37o C in a bioreactor with a diameter of 125 mm and high of 165 mm, with a substrate volume of 2000 ml. Chemical reactions and thermohydraulic formulations were carried out using the species transport, multiphase Eulerian model, and k- RNG turbulence model. It was found that the mixer speed had a significant effect on the rate of biogas production, which at a speed of 200 rpm gives the highest production rate of methane and carbon dioxide but the lowest hydrogen. It is concluded that there is an optimum rotational speed in the stirring process, which gives maximum biogas production.